A new approach to Grits waste management as filler in gypsum plasters - Souza, Saulo V.M. [UNESP]; Tolosa, Gabrieli R. [UNESP]; Bacarin, Giovani B. [UNESP]; Dognani, Guilherme [UNESP]; Okimoto, Fernando S. [UNESP]; Cabrera, Flávio C.; Job, Aldo E. [UNESP] (Emerald, 2022)
The reuse of industrial waste plays a crucial role in avoiding environmental impacts caused by incorrect disposal. The industrial production commonly generates huge volumes of wastes and also, increase costs associated to waste management and landfills maintenance. This study investigates the reuse of Grits waste, from cellulose kraft industry, as filler on gypsum plaster. The samples were prepared in proportions of 100/0, 85/15, 75/25 and 50/50 Gypsum/Grits and, tested at 7, 14, 21, 28 days. The mechanical resistance with incorporation until 25wt% of Grits as filler is over than the regulatory standards recommendations. Flexural and compression strength tests for 15wt% of gypsum replaced achieving 4.5 MPa and 8.3 MPa, respectively. The manufacture of Gypsum/Grits became a viable solution for waste management and, has a great potential of enabling fabrication of gypsum plaster board, a low cost and more sustainable new material.
Keywords: Industrial waste; Recycling and reuse materials; Tensile properties; Waste management